Determinants of Household Dietary Diversity in Bangladesh (Global Journal of Human-Social Science, 2019)
Dietary diversity is considered crucial for household welfare and also for carrying out other development activities The emerging interest in household dietary diversity against dietary quantity presents an opportunity to estimate household food security Based on secondary data probit regression model was used to estimate the determinants of household dietary diversity in Bangladesh The result suggests that household size literacy of household head total amount of land married household head total amount of remittance received and income of household head were major determinants in attainment of high dietary diversity Government policies and intervention programs targeting the above variables may improve household dietary diversity which in turn may improve household food security
Keywords: determinants; food security; household dietary diversity